If it's not what You are looking for type in the equation solver your own equation and let us solve it.
w/3=3(w-1)-1
We simplify the equation to the form, which is simple to understand
w/3=3(w-1)-1
Simplifying:
+ 0.333333333333w=3*(w-1)-1
Reorder the terms in parentheses
+ 0.333333333333w=+(+3w-3)-1
Remove unnecessary parentheses
+ 0.333333333333w=+3w-3-1
We move all terms containing w to the left and all other terms to the right.
+ 0.333333333333w-3w=-3-1
We simplify left and right side of the equation.
-2.66666666667w=-4
We divide both sides of the equation by -2.66666666667 to get w.
w=1.5
| 104-3x=5x+15 | | 90x+16=14+94x | | 0.08x+0.06(x+9)=1.24+2.3 | | -7+4w=-23 | | 7x-4(-5x-1)=4 | | 3x+8=57-10x | | 7x+8y=7 | | 40/184= | | 40*184= | | 3n+6=0 | | -2x-8y=1 | | 15=9p-6-5p | | 2(x+7)=18 | | -4a+3a-6a=-4 | | -73+3=15+11x | | 11b-4-b=30 | | 4-(.5)(x+5)=16 | | 2t+5=-1 | | 44.88/103.524=x | | 2x^2+15=593 | | n*10=126 | | 3b+5=23 | | -125y^6+150y^5-45y^4=0 | | n+40=54 | | 86/2 | | 38/2 | | 3/x=15/25 | | -102-9x=-98-7x | | -8(4)= | | 25a^6+20a^5+4a^4=0 | | 6x+3y=1 | | -5(-7+5x)=-190 |